2019
DOI: 10.1155/2019/2567198
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Seeds Improve Aging-Related Endothelial Dysfunction in Wistar Rats

Abstract: Vascular aging is characterized by functional and structural changes of the vessel wall, including endothelial dysfunction, with decreased endothelial NO⋅ bioavailability and elevated vasoconstrictor and inflammatory mediator production, vascular rigidity, and tone impairment. Moringa oleifera (MOI) is a little tree, and different parts of which are used in traditional medicine in tropical Africa, America, and Asia for therapeutic applications in several disorders including cardiovascular disease. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…Isorhamnetin also showed protective effects on endothelial cell line EA.hy926 and caused upregulation of eNOS expression 118 . Further, Quercetrin affected endothelial NO ⋅ signaling by inhibiting both arginase-1 activity and expression 119 .…”
Section: Discussionmentioning
confidence: 96%
“…Isorhamnetin also showed protective effects on endothelial cell line EA.hy926 and caused upregulation of eNOS expression 118 . Further, Quercetrin affected endothelial NO ⋅ signaling by inhibiting both arginase-1 activity and expression 119 .…”
Section: Discussionmentioning
confidence: 96%
“…A study revealed that administration of MO seed powder in a 750 mg/kg/day dose for 4 weeks gave protective effects to the endothelium function of aged rats. It was suggested that MO improved endothelium relaxation by increasing Akt signaling, activating endothelial NO synthase and down-regulating arginase-1 ( Randriamboavonjy et al, 2019 ). Phytochemical analysis was not performed in this study, but the endothelium improvement effects were most likely due to polyphenol, glucosinolate, and isothiocyanate compounds contained in MO.…”
Section: Role Of Mo In Cardiovascular Diseasesmentioning
confidence: 99%
“…Endothelial dysfunction is a condition that precedes the development of atherosclerosis and CVD [ 38 ]. Endothelial dysfunction is characterized by reduced bioavailability of NO, an important vasodilator molecule produced by endothelial cells [ 35 ]. Typically, reduction in NO bioavailability is associated with increased production of reactive oxygen species and abnormal inflammatory response [ 3 , 27 , 32 , 57 ].…”
Section: Vascular Effectmentioning
confidence: 99%
“…The effects of Moringa supplementation on aging-associated endothelial dysfunction have been evaluated in rats [ 35 ]. This study [ 35 ] demonstrated a reduction in endothelium-dependent relaxation of arteries in aged rats compared to young/adult rats. However, an improvement of such parameters was returned after Moringa supplementation in aged rats.…”
Section: Vascular Effectmentioning
confidence: 99%